COST-EFFECTIVENESS ANALYSIS OF ANTICOAGULANT USAGE IN COVID-19 PATIENTS AT 45 KUNINGAN HOSPITAL - Juju Jumiati; Yusi Anggriani; Yati Sumiyati; Umar Santosa (Medical Sains : Jurnal Ilmiah Kefarmasian, 2023)
Cost-effectiveness analysis (CEA) is a pharmacoeconomic method that compares prices from all sources consumed (cost) with the outcome value of a program or intervention to obtain objective answers to the selection of drugs that are effective in terms of benefits and costs. COVID-19, or Coronavirus Disease 2019, is caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARSCoV-2) and causes acute respiratory distress, including fever, coughing, and shortness of breath. Fondaparinux, aside from heparin and enoxaparin, can be given as an anticoagulant therapeutic option in hospitalized COVID-19 patients, according to the third edition of the COVID-19 care recommendations. This study aimed to find the most cost-effective therapy among heparin, enoxaparin, and fondaparinux in COVID-19 patients at the RSUD’45 Kuningan. It also applied descriptive non-experimental research methods with retrospectively collected data. The intervention that had been studied was the administration of anticoagulant medication, where the effectiveness of the drug was observed in the reduction of D-dimer levels to normal levels. Meanwhile, the costs were observed from the perspective of a healthcare provider, specifically the RSUD’45 Kuningan. The study sample included 107 patients, with 13 receiving heparin, 41 receiving enoxaparin, and 53 receiving fondaparinux. Bivariate analysis using the chi-square test revealed no significant difference between the drug groups in the proportion of patients who improved and did not improve (sig. value = 0.610)...